Sensitivity enhancement of optical fiber sensor for limonene sensing applications by using tapered optical fiber - Anbalagan, Thanigai (2024)
Evanescent wave sensing has led to significant advancements in various fields, including the development of optical fiber sensors (OFS). A simple and low-cost optical fiber sensor based on evanescent wave coupling of light into the core modes of plastic optical fiber (POF) coated with Zinc Oxide (ZnO) nanorods is reported here. The main objective of this research is to study the potential of optical sensing characteristics in the characterization of limonene concentration. Current detection methods for limonene sensing, which is one of a liver disease biomarker, lack sensitivity, and there is a need for a more accurate biomarker for early diagnosis. Study on the limonene concentration characterisation by using a fiber-optic sensor has not been conducted and published before. In this work, the sensor's performance was evaluated through changes in refractive index and light intensity. The study involved optimization of the sensor model, optical and electrical characterizations, and performance validations through mathematical analysis. The POF sensor’s sensing region was successfully developed using chemical etching and hydrothermal synthesis. Two POF design parameters were varied: tapered waist diameter and sensing region length. The sensor's performance was evaluated using three different lengths: 1 cm, 2 cm, and 3 cm. The effect of sensor diameter differences was also investigated, which included a study of sensor diameters of 0.70mm, 0.65mm, 0.60 mm, 0.55mm, 0.50mm, and 0.45mm. The experiment was also conducted using three different LEDs: blue, green, and red together with five different limonene concentrations of 20%, 40%, 60%, 80% and 100%. ZnO nanorods’ growth which is horizontal and vertical oriented nanoparticles with time of 10 hours leads to the best sensitivity of the fiber sensors. The best sensor design was discovered to be a vertically oriented ZnO coated sensor with a 0.45 mm tapered waist diameter, a 3 cm sensing region length, and a red LED light source. The sensitivity obtained was 6.85V/RIU, with the linearity of 99%. Limit of detection and standard deviation achieved by 0.03% and 0.06V respectively. This research lays the foundation for further comprehensive assessments and advancements in the field of optical sensing for limonene sensing.